Protecting Poor and Vulnerable Households in Indonesia - World Bank (World Bank, Jakarta, 2013)
Despite strong economic growth and falling poverty over the last decade, many households continue to live on the edge of poverty. The last decade in Indonesia has seen a return to strong economic growth, and the poverty rate has fallen from 23.4 percent (1999) to 12.5 percent (2011). The falling overall poverty rate, however, partially masks a high degree of vulnerability: much of Indonesia's population is clustered just above the poverty line, consuming approximately Rp 233,000 per month in 2011 (about US$ 27 at 2011 nominal exchange rates). Around 24 percent of Indonesians live below the official near-poor line (with consumption of approximately 1.2 times the poverty line) while 38 percent of the population lives below 1.5 times the poverty line and is almost equally vulnerable. Even relatively small shocks to these vulnerable households can be enough to push them into poverty. This report, the first comprehensive assessment of its kind in Indonesia, assesses the extent to which current social assistance programs are providing an effective social safety net for poor and vulnerable households. The government and its development partners require an analytical base to inform their decisions about social assistance policy reform and program design and delivery. To support this, the report uses all available qualitative and quantitative data (including the most recent) to assess the extent to which the current collection of Social Assistance (SA) programs is providing effective safety net functions: protecting the poor and vulnerable; promoting good behaviors, and enabling reforms effectively and efficiently.